Inventory and ethnobotanical assessment of plant species in Lagos State University, Ojo campus, Lagos, Nigeria - Abosede A. Adu; Olubunmi J. Sharaibi; Olutoyin J. Aderinola (AOSIS, 2017)
Inventory and ethnobotanical assessment of plant species growing on Lagos State University (LASU) Ojo main campus, Lagos State, Nigeria, were carried out. The aim was to document the vegetation composition and ethnobotanical uses of plants in the study area with a view to developing strategies for their conservation. Plant species with their frequency of occurrence were compiled and their representatives were collected for proper identification. Ethnobotanical assessment was carried out through oral interviews of herbalists, herb sellers and others with experience in traditional medicine. A total of 35 plant species belonging to 25 families were recorded from the survey. Poaceae has the highest number of species; Anacardiaceae, Asteraceae, Asparagaceae, Combretaceae, Euphorbiaceae, Malvaceae and Moraceae were all represented with two species each while the remaining 17 families were represented with one species each. Murraya paniculata recorded the highest frequency of occurrence within the study area with 165 individual plants followed by Ficus benjamina with 134 plants, then Ixora coccinea with 121 plants and Terminalia ivorensis with 103 plants. Anarcardium occidentale, Araucaria heterophylla and Ficus carica recorded the lowest frequency of occurrence with two plants each. The trees were the dominant plant habit (46%) followed by the shrubs (23%), grasses (17%) and herbs (14%). The plant species identified are of significant ethnobotanical uses ranging from food to medicine and ornamental. Effective conservation strategies for these plants include enacting laws against indiscriminate tree cutting, encouraging afforestation, proper maintenance of the parks and gardens and establishment of medicinal plant farms.